THE INFLUENCE OF PROBLEM-BASED LEARNING AND DISCOVERY LEARNING MODELS ON STUDENT LEARNING OUTCOMES IN CLASS XI HIGH SCHOOL REACTION RATE MATERIAL - sianturi, ranti evi sondang; Tarigan, Simson (Jurnal Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the influence and differences of Problem Based Learning and Discovery Learning learning models on student learning outcomes on reaction rate material. This research was conducted at SMA Negeri 1 Kualuh Hulu in the 2022/2023 school year. This type of research is quasi-experimental with pretest-postest control group design. The population in this study was all grade XI students of SMA Negeri 1 Kualuh Hulu. The sample in this study is class XI 1 as experimental class I which is taught using a problem-based learning model and class XI 6 as an experimental class II which is taught using a discovery learning learning model. Sampling in this study using purposive sampling. The instrument in this study is an objective test in the form of multiple choice as many as 20 questions that have been tested by validators and have been tested for validity, level of difficulty, differentiation, reliability. The results showed that there was an influence of the problem-based learning model on learning outcomes, namely the pretest value of 44.5 and the postest value of 88.83 and the influence of the discovery learning model, namely nailai pretest 41.83 and postets value of 82.83 and there were differences in the learning outcomes of experimental class I and experimental class II, namely with a count of 3.4843 > table 2.002